Sedition Promoters and Their Threat to The Stability of The Country in Sunnah | دعاة الفتن وخطرهم على استقرار الوطن في السنة النبوية - Hakima Ahmed Hafidi; Faouzi Ben Mouhoub (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
The Prophet’s Sunnah stressed on highlighting the tumultuous strife that will afflict the Islamic Ummah with the characteristics of those arrogant and fanatics. This research focuses on highlighting the prophetic directives that warned from temptations against the contemporary reality of Muslims, by analyzing what was mentioned in some hadiths related to epics which advised on ways to predict the occurrence of seditions and the ways to ward off them by taking lessons from them since they are considered as a treatment of the prophet against seditions. This topic aims to explore the characteristics of sedition advocates in the Prophetic Sunnah, ways to prevent sedition based on Sunnah, and the danger of sedition advocates to the stability of the country. The article employ the analytical and inductive approach. The first was used to analyze some of the narrations related to the chapters on seditions and epics and understanding them in accordance to what our Prophet intended as the main way to prevent the seditions. The second was used to trace the characteristics the seditions’ advocates and illustrating their danger on the five purposes of Sharia. This article indicates that the advocates of sedition are the hard-liners among the Islamists, and the alienated ones among the secularists alike, and they both pose the greatest threat at the present time on the security and stability of nations in the Islamic world, and their danger to the nations is very clear, especially at the present time where chaos prevailed in most of the Islamic countries; Which exposed it to the risk of disintegration at the hands of those who adopted those speeches from the enthusiastic youth. Furthermore, the noble Prophet's Sunnah contains the adequate treatment and healing balm for all the dangers and strife that befell or befall the nation.